2016
DOI: 10.1002/app.43515
|View full text |Cite
|
Sign up to set email alerts
|

Rapid swelling and deswelling of semi‐interpenetrating network poly(acrylic acid)/poly(aspartic acid) hydrogels prepared by freezing polymerization

Abstract: Hydrogels with semi‐interpenetrating networks composed of poly(acrylic acid) (PAAc) and poly(aspartic acid) (PASP) have great potential for pharmaceutical and biomedical applications. In this study, we aimed to synthesize semi‐interpenetrating PAAc/PASP hydrogels with improved swelling–deswelling properties via two‐step polymerization, in which the first step of polymerization was performed at 37 °C for 15 min and the second step, the freezing polymerization, was performed at −20 °C for 24 h. The synthesized h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…These mixtures contributed both swelling and mechanical strength, although no synergy was detected, and each individual polymer retained its own intrinsic properties. ,, Another approach is to prepare semi-IPNs as a single solution to obtain a greater synergy. In the formation of semi-IPNs, a cross-linked polymer is normally mixed with a non-cross-linked polymer, followed by the in situ cross-linking of the later. ,, This method enhances the structural features of the network, giving rise to high water retention even under mechanical stress, which is lacking in neat IPN systems. Most of the literature suggesting semi-IPNs relates however to the preparation of limited amounts of hydrogels for drug-delivery applications. These semi-IPNs thus contain a substantial amount of synthetic polymer since the area of use does not require the development of large-scale inexpensive biobased SAP materials.…”
Section: Functionalization Of Proteins For Improving Water Affinitymentioning
confidence: 99%
“…These mixtures contributed both swelling and mechanical strength, although no synergy was detected, and each individual polymer retained its own intrinsic properties. ,, Another approach is to prepare semi-IPNs as a single solution to obtain a greater synergy. In the formation of semi-IPNs, a cross-linked polymer is normally mixed with a non-cross-linked polymer, followed by the in situ cross-linking of the later. ,, This method enhances the structural features of the network, giving rise to high water retention even under mechanical stress, which is lacking in neat IPN systems. Most of the literature suggesting semi-IPNs relates however to the preparation of limited amounts of hydrogels for drug-delivery applications. These semi-IPNs thus contain a substantial amount of synthetic polymer since the area of use does not require the development of large-scale inexpensive biobased SAP materials.…”
Section: Functionalization Of Proteins For Improving Water Affinitymentioning
confidence: 99%
“…[7][8][9] Among various types of hydrogels, poly acrylate polymers such as poly acrylic acid (PAA), with distinctive absorptivity properties, have the most versatile structure to enhance their practical utility in everyday life applications such as filtration, water remediation, diapers and hygiene products, cosmetics, wound dressings, medical waste solidification and metal ion removal. [10][11][12][13][14] From extensive studies evaluating different properties of PAA hydrogels, such as swelling, 15 adhesion, 16 diffusion, 17 physico-chemical 18 and mechanical 19 properties, it has been revealed that the greatest concern about these types of hydrogels is their poor mechanical properties. 11,[20][21][22] The poor mechanical properties of PAA hydrogels, which relate closely to their large volume change subsequent to swelling, count as a marked weakness in consideration for adoption for high-tech applications, and have limited their specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, characteristic peaks at 1668 cm −1 (C=O stretching of amide group), 1725 cm −1 (C=O stretching of carboxyl group), 1598 cm −1 (COO − asymmetric stretching), 1411 cm −1 (COO-symmetric stretching mode), and 1450 cm −1 (C–H bending) could be observed in the IR spectra of the IPN0 hydrogels. This result proved that PAm and PAA had been successfully polymerized in the hydrogel networks [28].…”
Section: Resultsmentioning
confidence: 63%